Coping with choices to die - Prado, C. G. (Cambridge : Cambridge University Press, 2011)
'This book examines the reactions of the friends and family of those who elect to die due to terminal illness. These surviving spouses, partners, relatives, and friends, in addition to coping with the death of a loved one, must also deal with the loved one's decision to die, thus severing the relationship. C. G. Prado examines how reactions to elective death are influenced by cultural influences and beliefs, particularly those related to life, death, and the possibility of an afterlife. Understanding the role of these cultural influences on the grieving processes of survivors is a crucial step in allowing them to accept both intellectually and emotionally the finality of elective death and to deal with the decision of their loved one'--
Includes bibliographical references (p. 177-183) and index.
Keywords: Older people -- Suicidal behavior; Suicide -- Moral and ethical aspects; Euthanasia -- Moral and ethical aspects